2020
DOI: 10.1021/acs.orglett.0c03632
|View full text |Cite
|
Sign up to set email alerts
|

Copper-Catalyzed Formal Transfer Hydrogenation/Deuteration of Aryl Alkynes

Abstract: A copper-catalyzed reduction of alkynes to alkanes and deuterated alkanes is described under transfer hydrogenation and transfer deuteration conditions. Commercially available alcohols and silanes are used interchangeably with their deuterated analogues as the hydrogen or deuterium sources. Transfer deuteration of terminal and internal aryl alkynes occurs with high levels of deuterium incorporation. Alkyne-containing complex natural product analogues undergo transfer hydrogenation and transfer deuteration sele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 58 publications
2
24
0
Order By: Relevance
“…In a previous study by our group, we performed a Cucatalyzed alkyne transfer hydrogenation reaction using isopropanol as one of the H-sources. [41] This study revealed that hydrometalation of the alkene likely occurs in a reversible manner, similar to what is depicted for both the desired anti- We discovered that full conversion of alkene 1 can be achieved by increasing the catalyst loading to 3 mol% (entry 8, 90 % yield of 2 a, > 20 : 1 regioisomeric ratio). Consistent with entry 7, no alkene isomerization by-product was detected when using [D 8 ]isopropanol.…”
supporting
confidence: 67%
See 1 more Smart Citation
“…In a previous study by our group, we performed a Cucatalyzed alkyne transfer hydrogenation reaction using isopropanol as one of the H-sources. [41] This study revealed that hydrometalation of the alkene likely occurs in a reversible manner, similar to what is depicted for both the desired anti- We discovered that full conversion of alkene 1 can be achieved by increasing the catalyst loading to 3 mol% (entry 8, 90 % yield of 2 a, > 20 : 1 regioisomeric ratio). Consistent with entry 7, no alkene isomerization by-product was detected when using [D 8 ]isopropanol.…”
supporting
confidence: 67%
“…The role of the alcohol and/or silane in Cu-catalyzed alkene and alkyne hydrofunctionalization processes has been previously studied. [28,[38][39][40][41][42][43] Given that changing temperature, concentration and solvent did not lead to an optimal reaction, we decided to explore other alcohol-OD sources. The alcohol-OD reagent is important in the reaction because it is involved in the deuterodecupration of intermediates iii a and iii b (Scheme 2).…”
mentioning
confidence: 99%
“…Notably, this early report employs an inexpensive deuterium source, which is often incompatible with metal-catalyzed transfer deuterations because of the potential for catalyst poisoning or undesirable side products. The authors demonstrated selective deuterium incorporation in the β-position of methylsuccinic acid dimethyl ester (31).…”
Section: Rhodium and Ruthenium-catalyzed Reactionsmentioning
confidence: 99%
“…Another reaction that has been scarcely reported is a general alkyne transfer deuteration protocol. In 2020, the Clark group developed the first Cu‐catalyzed transfer deuteration of aryl alkynes [31] . The reaction employs dimethoxy(methyl)silane‐ d 1 and 2‐propanol‐OD (or ethanol‐OD) as the deuterium sources and ( R or S )‐DTBM‐SEGPHOS as a ligand for copper.…”
Section: Recent Advances In Catalytic Transfer Deuteration (Td) and Transfer Hydrodeuteration (Thd)mentioning
confidence: 99%
“…The sentence that was intended to be included is as follows:Recently Clark has demonstrated a Cu-catalysed route for the preparation of alkanes and fully deuterated alkanes from alkynes. 1 The Royal Society of Chemistry apologises for these errors and any consequent inconvenience to authors and readers.…”
mentioning
confidence: 99%